PRESENTATION OF INFORMATION ABOUT USING EAST DISTRICT BELITUNG ADOBE PHOTOSHOP 7.0 - Wiwiek Lestari; Yuce Yulina, Skom., MMSI (Jurnal Sistem Informasi, 2004)
The Internet is a medium that is widely used by communities to receive and distributeinformation. This increase was marked by numerous web sites that appear as amedium of communication and education that is able to accommodate and serve thevarious forms of information, and interests.The new East Belitung province was inaugurated on May 25, 2003 was felt necessaryto introduce regions to the general public using the Internet media that is by makingthe web simple and attractive and provides convenience to users who use the servicesof such web sites.